2007
DOI: 10.1016/j.gca.2007.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Fluorapatite surface composition in aqueous solution deduced from potentiometric, electrokinetic, and solubility measurements, and spectroscopic observations

Abstract: International audienceThe surface chemistry of fluorapatite in aqueous solution was investigated using electrokinetic techniques, potentiometric titrations, solubility measurements, and attenuated total reflection infrared spectroscopy. All methods indicate the formation of Ca/F depleted, P enriched altered layer via exchange reactions between H+ and Ca2+, and OH? and F? at the fluorapatite (FAP) surface. Observations suggest that this leached layer has a di-calcium phosphate (CaHPO4) composition and that it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 53 publications
(58 reference statements)
3
43
0
9
Order By: Relevance
“…Several recent studies reported that due to metal exchange reactions, the composition of the near-surface of multi-oxide minerals depends strongly on the composition of its surrounding aqueous phase (e.g. Pokrovsky and Schott, 2000;Chaïrat et al, 2007;Oelkers et al, 2009). In an attempt to extend these concepts to phyllosilicates, we have performed a series of batch potentiometric titration experiments and electrokinetic measurements on biotite surfaces as a function of aqueous solution pH from 1 to 12.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies reported that due to metal exchange reactions, the composition of the near-surface of multi-oxide minerals depends strongly on the composition of its surrounding aqueous phase (e.g. Pokrovsky and Schott, 2000;Chaïrat et al, 2007;Oelkers et al, 2009). In an attempt to extend these concepts to phyllosilicates, we have performed a series of batch potentiometric titration experiments and electrokinetic measurements on biotite surfaces as a function of aqueous solution pH from 1 to 12.…”
Section: Introductionmentioning
confidence: 99%
“…As presented in Figure 13, two nearly straight lines approximate the Roozeboom curve. This implies that in the case of the JBM-HAP solid solution series, even a negligible amount of aqueous phosphates in the system can alter the thermodynamic equilibrium to promote the formation of HAP-rich solids [32,37,38]. The increase in the phosphate content in the structure of JBM improves its stability.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, the solution [29]. Additionally, the experimental conditions could significantly affect the apatite dissolution [30].…”
Section: Change Of Solution Ph and Elemental Concentrations With Timementioning
confidence: 99%